ECONOMIC AND MATHEMATICAL MODELING OF THE FUNCTIONING OF AN INDUSTRIAL ENTERPRISE - Natalia Lokhman; Tatiana Beridze; Zoya Baranik; Alla Cherep; Iryna Dashko; Oxana Hamova (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
The purpose of the article is to model the activities of an industrial enterprise as an independent economic unit in order to increase the profit of the enterprise in terms of economic efficiency. Method. In the course of the research the methodology of economic-mathematical modeling was applied. The enterprise is considered as a complex system — a sublimated enterprise, an economic object. The use of simulation methods on specific statistical material of the industrial enterprise «PivdGOK» is given. The application of the methods of digital economy allowed to obtain the relevant indicators of the enterprise and to obtain appropriate visual and graphical representations of the results. Results. The economic and mathematical model of the industrial enterprise of PJSC «PivdGOK» is constructed, it allowed to generalize results of activity of the industrial enterprise. Analytical relations concerning the activity of an industrial enterprise are obtained, namely a systematic study of the relationship between costs, volume of activity and profit of the enterprise. Scientific novelty. For the first time the economic-mathematical model of activity of the industrial enterprise in the sense of definition of its effective functioning as economic unit is constructed. Obtained in the implicit form of the dependence of profit at a given economic efficiency allowed us to investigate this relationship in order to build a simulation model. Practical significance. The use of Mathcad software allowed to building a simulation model of the industrial enterprise. An analytical expression of the connection between economic efficiency and profit is obtained, which allows to carry out a corresponding analysis of the activity of an industrial enterprise. It is shown under what conditions it is possible to achieve the greatest profit at a given economic efficiency. The use of digital modeling allowed to numerically obtain the optimal values of profit and graphically display the results. Graphical representation of the obtained results allows for visual analysis.